Pendugaan Erosi Tanah dan Perencanaan Tutupan Lahan Hulu DAS Jeneberang, Sulawesi Selatan - Balqis Nur Aisyah; Dwi Putro Tejo Baskoro; Kukuh Murtilaksono (Institut Pertanian Bogor, 2022)
Soil erosion is the main cause of land degradation. Jeneberang watershed is one of the priority watersheds in Indonesia. It has a big problem related to erosion in the upstream area. Jeneberang watershed is important area, its function is as water catchment for Bili-bili reservoir. It is served for flood control, irrigation water sources, water and hydroelectric energy supply. The aims of this study were to analyze the soil erosion prediction based on existing condition; develop an ideal land cover scenario to decrease soil erosion; and suggest land cover planning recommendations based on tolerable soil loss indicators in the upstream of Jeneberang watershed. This study was conducted using map overlay method to determine the value of the erosion factor. Erosion was predicted based on Universal Soil Loss Equation (USLE). Land scenarios and simulations was calculated by estimating the erosion in forest area and spatial planning land cover. The result showed that soil erosion of existing condition was approximately 813.1 tons/ha/year. The tolerable soil loss was only 22.9 tons/ha/year. The landuse scenario that chooses the lowest presumed erosion result is the implementation of spatial planning of Gowa district 2012-2032 with soil conservation technique applied. It can reduce erosion and sediment as 96.6% in upstream Jeneberang watershed. Keywords: erosion, Jeneberang watershed, scenario, landuse